Universal Free School Breakfast: A Qualitative Process Evaluation According to the Perspectives of Senior Stakeholders - Harvey-Golding, Louise; Donkin, Lynn Margaret; Defeyter, Margaret Anne (Frontiers in Public Health, 2016)
In the last decade the provision of school breakfast has increased significantly in the UK. However, there is an absence of knowledge regarding senior stakeholder views on the processes and potential outcomes on different groups, within the communities served by school breakfast programs. The purpose of this study was to examine the views and experiences of senior level stakeholders and thereby provide an original qualitative contribution to the research. A sample of senior level stakeholders were recruited, including senior officers, directors and elected members, from within a Local Authority (LA) involved in the leadership, implementation and delivery of a council-wide universal free school breakfast (USFB) program, and from the senior staff body of mainstream primary and special schools, participating in the program. A grounded theory analysis of the data collected identified issues encountered in the implementation and delivery, and views on the funding and future of a USFB program, in addition to perceived outcomes of children, parents, families, schools and the wider community. The results refer to both positive and negative issues and implications associated with the program, according to the perspectives of senior level stakeholders. Perceived positive outcomes included benefits to children, families, schools and the community. For instance, alleviating hunger, improving health outcomes, and conferring financial benefits, with the potential to cumulate in overall improvements in educational, social and behavioral outcomes. Reported negative implications included the absence of an effective communication strategy in implementing the USFB program; in addition to concerns about the impacts of ‘double-breakfasting’ on obesity levels among children, particularly in less deprived communities. Findings were validated using theoretical sampling and saturation, triangulation methods, member checks, and inter-rater reliability measures. In presenting these findings, this paper provides a unique qualitative insight into the processes, issues and outcomes of a council-wide universal free school breakfast program within a socioeconomically deprived community, according to the perceptions of senior level stakeholders.